Delayed Manipulation after Collagenase Clostridium Histolyticum Injection for Dupuytren Contracture. (September 2015) - Kaplan, F. Thomas D.; Badalamente, Marie A.; Hurst, Lawrence C.; Merrell, Gregory A.; Pahk, Raymond
Background: Collagenase clostridium histolyticum (CCH) injection for Dupuytren contracture was approved in the USA in 2010. Current FDA guidelines stipulate that finger manipulation occurs the day following injection. To investigate the safety and efficacy of delaying manipulation to 2 or 4 days following CCH injection, we conducted a prospective, randomized trial at two sites. Methods: Patients with Dupuytren contracture involving the metacarpophalangeal (MCP) joint ≥20° caused by a palpable cord participated. All patients received one dose of CCH (0.58 mg/0.25 ml) and were followed for 90 days. The primary end point was the percent of patients maintaining clinical success (reduction of contracture to 0°–5°) at 90 days post-injection. Adverse events and change in Michigan Hand Questionnaire (MHQ) score were recorded as secondary end points. Results: Thirty-seven patients enrolled; 13 were manipulated on day 1, 11 on day 2, and 13 on day 4. At 30 days after injection, the percentage of patients obtaining reduction of contracture to <0°–5° extension was 92, 82, and 85 % in groups 1, 2, and 3, respectively, with no significant difference. At 90 days follow-up, the percentage of patients maintaining 0°–5° extension was 91, 82, and 83 % in groups 1, 2, and 3, respectively, with no significant difference. Adverse events were comparable to rates in prior studies. There were no serious adverse events. There was no statistical difference in MHQ scores between groups at any time point. Conclusions: Delaying manipulation to day 2 or 4 following CCH injection for MCP joint contractures does not increase adverse events or result in loss of efficacy. Level of Evidence: Therapeutic, Level II.